2019
DOI: 10.1039/c9tc00082h
|View full text |Cite
|
Sign up to set email alerts
|

N-, B-, P-, Al-, As-, and Ga-graphdiyne/graphyne lattices: first-principles investigation of mechanical, optical and electronic properties

Abstract: Graphdiyne and graphyne are carbon-based two-dimensional (2D) porous atomic lattices, with outstanding physics and excellent application prospects for advanced technologies, like nanoelectronics and energy storage systems. During the last year, B-and N-graphdiyne nanomembranes were experimentally realized. Motivated by the latest experimental advances, in this work we predicted novel N-, B-, P-, Al-, As-, Ga-graphdiyne/graphyne 2D lattices. We then conducted density functional theory simulations to obtain the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…For-example, to acquire the 3rd order force-constants for the graphene and C 3 N with a cutoff distance to 11th neighbors, one needs to conduct~200 and 700 DFT force-calculations, respectively. For low-symmetrical, nanoporous and anisotropic lattices, like C 7 N 6 and graphyne/graphdiyne [90] structures, which normally show low thermal conductivities, we do believe that the proposed methodology can exhibit a unique performance to predict the thermal conductivity conveniently and accurately, with the need for minimal computation resources.…”
Section: Resultsmentioning
confidence: 99%
“…For-example, to acquire the 3rd order force-constants for the graphene and C 3 N with a cutoff distance to 11th neighbors, one needs to conduct~200 and 700 DFT force-calculations, respectively. For low-symmetrical, nanoporous and anisotropic lattices, like C 7 N 6 and graphyne/graphdiyne [90] structures, which normally show low thermal conductivities, we do believe that the proposed methodology can exhibit a unique performance to predict the thermal conductivity conveniently and accurately, with the need for minimal computation resources.…”
Section: Resultsmentioning
confidence: 99%
“…[6] In order to develop new types of graphyne-based materials,m etal elements as an ew form of molecular functionality can be introduced into the framework of graphdiynes to afford metallated graphynes.T he first-principles density functional theory calculations have been used to explore the excellent mechanical, electronic and optical characteristics and thermal stability of N-, B-, P-, Al-, As-, and Ga-graphyne-based 2D lattices. [7] However,related research work on the structurally similar metallated graphynes is still in its infancyand bottomup large-area and free-standing metallated graphynes were never synthesized. [8] In ar elated context, Sun et al reported that the formation of 2D ÀCCÀAuÀCCÀ organometallic networks was observed under high-resolution scanning tunneling microscope through dehalogenative homocouplings of alkynyl bromides on an Au(111) surface at room temperature (RT) and slight annealing to 320 K. [8a] Besides,Y ang et al reported the formation of 2D organometallic Ag-bis-acetylide ÀCCÀAgÀCCÀ networks on Ag(111).…”
Section: Introductionmentioning
confidence: 99%
“…In order to develop new types of graphyne‐based materials, metal elements as a new form of molecular functionality can be introduced into the framework of graphdiynes to afford metallated graphynes. The first‐principles density functional theory calculations have been used to explore the excellent mechanical, electronic and optical characteristics and thermal stability of N‐, B‐, P‐, Al‐, As‐, and Ga‐graphyne‐based 2D lattices [7] . However, related research work on the structurally similar metallated graphynes is still in its infancy and bottom‐up large‐area and free‐standing metallated graphynes were never synthesized [8] .…”
Section: Introductionmentioning
confidence: 99%
“…GYs materials possess fascinating structures and unique electronic properties, which can be widely applied in the fields of catalysis, anode materials, optoelectronic devices, biomedicine, and sensing, etc. [23,[25][26][27][28][29] Interestingly, the research on the NLO properties of GY molecules has attracted significant attention. [30][31][32] In particular, several studies have indicated that the GYs structures are very suitable for designing novel NLO materials.…”
Section: Introductionmentioning
confidence: 99%